Recent Advances of Electrocatalyst and Cell Design for Hydrogen Peroxide Production - Huang, Xiao; Song, Min; Zhang, Jingjing; Shen, Tao; Luo, Guanyu; Wang, Deli (Nano-Micro Letters, 2023)
Electrochemical synthesis of H2O2 via a selective two-electron oxygen reduction reaction has emerged as an attractive alternative to the current energy-consuming anthraquinone process. Herein, the progress on electrocatalysts for H2O2 generation, including noble metal, transition metal-based, and carbon-based materials, is summarized. At first, the design strategies employed to obtain electrocatalysts with high electroactivity and high selectivity are highlighted. Then, the critical roles of the geometry of the electrodes and the type of reactor in striking a balance to boost the H2O2 selectivity and reaction rate are systematically discussed. After that, a potential strategy to combine the complementary properties of the catalysts and the reactor for optimal selectivity and overall yield is illustrated. Finally, the remaining challenges and promising opportunities for high-efficient H2O2 electrochemical production are highlighted for future studies. Highlights: 1 Fundamental principles for designing highly efficient two-electron oxygen reduction reaction catalysts are briefly reviewed. 2 Strategies to integrate the components into an efficient device for hydrogen peroxide production are discussed. 3 The challenges and perspectives for catalyst and cell design are discussed.